2017
DOI: 10.1007/s10142-017-0554-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of miR061 and its target genes in grapevine responding to exogenous gibberellic acid

Abstract: MicroRNAs (miRNAs), as an important growth regulator, are also involved in gibberellic acid (GA) signaling, revealing much relationship between miRNAs and GA in various plant responses. Grape is highly sensitive to GA, which plays a significant regulatory role in regulation of flower development, berry expansion, berry set, berry ripening, and seedlessness induction; further, it was found that grapevine miR061 (VvmiR061) is a GA responsive miRNA. In this study, grapevine REV (VvREV) and HOX32 (VvHOX32), two ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Therefore, GA is recognized as a key phytohormone regulator for seed embryo development and stone-hardening in grape. Previous studies showed that several VvmiRNAs were differentially expressed during grape berry development in response to GA application (Ren et al 2014, Han et al 2014, Wang et al 2017. However, stone-hardening stage-speci c VvmiRNAs and their regulatory networks during grape berry development remain imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, GA is recognized as a key phytohormone regulator for seed embryo development and stone-hardening in grape. Previous studies showed that several VvmiRNAs were differentially expressed during grape berry development in response to GA application (Ren et al 2014, Han et al 2014, Wang et al 2017. However, stone-hardening stage-speci c VvmiRNAs and their regulatory networks during grape berry development remain imperative.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of exogenous GA application on the induction of flower development, seedless cultivars, berry enlargement and fruit ripening of grapevine have recently been reported [18, 20]. However, the molecular mechanisms by which GA-signaling mediates flower and fruit set initiation in grapevines are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Phytohormones, such as GA, are known to be essential for the regulation of grape flower development, berry expansion, ripening, and seedless berry induction, and the exogenous application of GA can trigger fruit parthenocarpy and early ripening in various grapevine cultivars [15, 18, 19]. Several reports demonstrated that different miRNA families (miR061, miR156, miR159, miR160, miR164, miR167, miR172, and miR319) and their target genes are implicated in GA signal during floral transition and fruit set development [8, 9, 20]. For instance, Arabidopsis AtmiR159 acts as a homeostatic regulator of GA signaling to direct the cleavage of genes encoding AtGAMYB proteins, causing a defect in anthers development and a subsequent reduction in floral fertility [21].…”
Section: Introductionmentioning
confidence: 99%
“…RNA was isolated from grapevine plant tissue using standard molecular biology protocols and following manufacturer’s instructions, as previously described [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…In plants, miRNAs play important roles in a number of physiological processes, such as growth development and biotic and abiotic stress responses [ 1 – 5 ]; they can regulate the expression levels of their target genes by cleavage. Other miRNAs emerged as promising approaches for plant breeding applications, such as crop improvement strategies [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%